أبو العباس أحمد بن عبد الله محب الدين الطبري التعريف به وبيان منهجه الحديثي في كتابه (غاية الإحكام في أحاديث الأحكام): Biographical Study of Abū al-`Abbās Aḥmad bin `Abdillāh Muḥib al-Dīn al-Ṭabarī and His Hadith Methodolgy in the Book of Gāyah al-Iḥkām fī Aḥādīṡ al-Aḥkām - Rachmat bin Badani Tempo (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the author of the book of Gayah al-Iḥkām fī Aḥādīṡ al-Aḥkām, namely Abū al-'Abbās Aḥmad bin 'Abdulāh al-Ṭabārī as one of the Shafi'i scholars and to reveal his character in the field of Hadith science through a study of the hadith methodology of the book. This research is a descriptive study with an inductive methodology. The results of the study show that: first, Abū al-'Abbās Aḥmad bin 'Abdulāh al-Ṭabārī is one of the very central Syafii scholars in the Shafii school and has been widely praised by scholars; second, his expertise in the field of hadith is evident through his book, Gayah al-Iḥkām, from the following points: (1) that this book is one of the books that collects the most ahkam hadiths, and its author is among the scholars who first wrote ahkam hadith books as a whole; (2) the main purpose of writing this book is to collect the narrations of the ahkam hadith without including the sanad, so that the author includes the authentic and hasan ahkam traditions, and this is the dominant one, although sometimes he also mentions weak hadiths and very rarely does he explain their weaknesses; (3) through this book, the author's expertise on the science of hadith is seen in his attention to hadith lafaz, explanations of garib hadith, syaraḥ musykil hadith, nasikh and mansūkh, laws of hadith and so on. This book is also more perfect because of the author's attention to the views of the school's scholars and a very systematic arrangement when describing their arguments on the problem of khilafiyah. Through this research, it also appears that the author mentions a lot of information that we don't have today..